Experimental investigations on Thermal Performance of Copper with Aluminium Based Finned Heat sinks for Electronics Cooling System - Loganathan, Arulmurugan; Mani, Ilangkumaran (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
An Experimental investigation on theÂ thermal performance of copper with aluminium based finned heat sinks for electronics cooling system was studied. The heat sinks have different material proportions containing major constituent of aluminium and minor constituent of copper. Considered with straight finned heat sink for the experiments for its easiness in fabrication and efficient heat transfer properties. The observational results for aluminium with copper alloy are compared with pure aluminium heat sink.Â  Heat sink geometry, fin pitch and its height were taken from the commercially available heat sinks. In this research work best heat sink geometry is chosen and cooked up with different volume of copper added with aluminium. Selected four different spots of heat sinks and the temperature raising characteristics were measured for natural convection. also the temperature is raised to a fixed temperature and the temperature lowering characteristics were measured in forced convection as the air circulation takes more heat to keep the heat sink temperature within the desired level.